MAṢDAR ṢARĪḤ DALAM KITAB MATAN AL-GĀYAH WA AT-TAQRĪB (ANALISIS MORFOSINTAKSIS) - Dhonni Dwi Prasetyo; Mohamad Yusuf Ahmad Hasyim; Hasan Busri (Lisanul Arab: Journal of Arabic Learning and Teaching, 2023)
Mashdar Sharih is a word that shows the meaning of an event/deed without beingaccompanied by a description of the time. The purpose of this study was to determinethe types of mashdar sharih in the of matan al-ghayah wa at-taqrib book in termsof morphology and syntax. This research is a qualitative research with libraryresearch design. The data is in the form of mashdar sharih in the matan al-ghayahwa at-taqrib book. Data collection techniques using documentation techniques. Inthis research, 60 mashdar sharih data were found in the matan al-ghayah wa at-taqrib book. Based on the type of mashdar sharih, there are 52 data of the mashdarghoiru mim type, 4 data of the mashdar mim type, and 4 data of the isim mashdartype. Based on the model pattern, there are 12 data with model pattern فَعْـلًا, 2 datawith model pattern فِـعْلًا, 1 data with model pattern فُعْـلًا, 2 data with model patternفَعَـلًا, 5 data with model pattern فِـعَـالًا, 1 data with model pattern فُــعْـلَـةً, 1 data withmodel pattern فِــعَالَــةً, 6 data with model pattern فُـعُـوْلًا, 3 data with model patter فَــعَـالًا,4 data with model pattern فَــعَـالَـةً, 3 data with wazan تَفْـعِيْلًا, 5 data with wazan إِفْعَـالًا, 3data with wazan تَفَـعُّـلًا, 1 data with model pattern اِفْـتِـعَالًا, 1 data with model patternاِنْـفِـعَالًا, 1 data with model pattern اِسْتِـفْـعَالًا, 2 data with model pattern مَـفْـعَلًا, and 2 datawith model pattern مُـفَاعَـلَةً. Based on the syntatic function, there are 7 data hadsyntatic function as fa'il, 4 data had syntatic function as naibul fa'il, 5 data hadsyntatic function as mubtada', 2 data had syntatic function as khobar, 4 data hadsyntatic function as maf'ul bih, 1 data had syntatic function as maf'ul muthlaq, 1 datahad syntatic function as maf'ul li-ajlih, 2 data had syntatic function as chaal, 2 datahad syntatic function as tamyiz, 1 data had syntatic function as mustatsna, 2 datahad syntatic function as isim laa li-nafyi al-jinsi, 1 data had syntatic function as isimkaana wa akhawatuha, 1 data had syntatic function as khobar kaana waakhawatuha, 6 data had syntatic function as majrur bi harf jar, 3 data had syntaticfunction as madhruf, 8 data had syntatic function as mudlaf ilaih, 1 data had syntaticfunction as na'at li al-marfu', 1 data had syntatic function as na'at li al-majrur, 3data had syntatic function as ma'thuf li al-marfu', 1 data had syntatic function asma'thuf li al-majrur, 2 data had syntatic function as badal li al-marfu' , and 2 datahad syntatic function as badal li al-majrur. Based on cases and grammaticalmarkers, there are 25 nominative case data with dlummah grammatical markers, 14accusative case data with fathah grammatical markers, and 21 genetive case datawith kasroh grammatical markers.